2021
DOI: 10.1002/agm2.12181
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of older adults at risk of frailty

Abstract: Background The integral part of the definition of frailty is the outcome associated with it. Older adults at risk of frailty are in the process of becoming frail. This study looked at the clinical characteristics and outcomes of older adults at risk of frailty. Methodology The study population was selected from outpatient department of the geriatric medicine department in a tertiary care hospital. Older adults identified as at risk of frailty were assessed at baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Specific to India, frailty has been assessed in different contexts; in patients with Chronic Kidney Disease (CKD) [ 30 ], in community-dwelling older adults [ 31 ], and in rural populations [ 32 ], and has been associated with worse outcomes. [ 33 ] Conventional determinants of frailty are age, sex, absence of social support, polypharmacy, multiple comorbidities, higher body mass index, and presence of psychological factors among others. [ 34 , 35 ] In our context, we hypothesized that additional factors such as SES and nutrition would have an impact on frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to India, frailty has been assessed in different contexts; in patients with Chronic Kidney Disease (CKD) [ 30 ], in community-dwelling older adults [ 31 ], and in rural populations [ 32 ], and has been associated with worse outcomes. [ 33 ] Conventional determinants of frailty are age, sex, absence of social support, polypharmacy, multiple comorbidities, higher body mass index, and presence of psychological factors among others. [ 34 , 35 ] In our context, we hypothesized that additional factors such as SES and nutrition would have an impact on frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is a part of frailty and means reduced muscle protein synthesis, a result of lower testosterone and IGF-1 and increased muscle protein breakdown due to chronic hyperglycemia and inflammation and is associated with insulin resistance. Frailty and its risk can be measured 1271,1272 . Management of frailty in diabetes includes optimal nutrition with adequate protein intake combined with an exercise program that includes aerobic, weight-bearing, and resistance training under medical supervision.…”
Section: B Diabetes and Geriatric Syndromesmentioning
confidence: 99%
“…Multiple studies from India have reported frailty in hospital and community settings [5][6][7][8]. Few studies from India have recently reported on IC as well [9,10].…”
Section: Introductionmentioning
confidence: 99%